Seasonal changes in cestode infection of Cyclops vicinus Uljanin, 1875 (Copepoda, Cyclopoida) in Lake Hazar (Elazig, Turkey) - Dorucu, Mustafa (Brill, 2007)
In this study, the seasonal variation of natural levels of infection in Cyclops vicinus Uljanin, 1875 with procercoids of cestodes was examined in Lake Hazar, Turkey from November 2005 to October 2006. The prevalence of infected C. vicinus was found to increase with water temperature (p < 0.01); a peak occurred in September, while relatively low levels were recorded between November and March. No statistically significant relation was determined between infection and pH values (p > 0.05). However, a statistically significant, negative correlation was found between infection and dissolved O-2 level (p < 0.05). Each infected Cyclops carried only one procercoid.